The sonopartogram: a novel method for recording progress of labor by ultrasound. (4th February 2014) - Hassan, W. A.; Eggebø, T.; Ferguson, M.; Gillett, A.; Studd, J.; Pasupathy, D.; Lees, C. C.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2014; 43: 137–138